2016
DOI: 10.3390/ijms17101671
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of β-Conglycinin (7S) with Different Phenolic Acids—Impact on Structural Characteristics and Proteolytic Degradation of Proteins

Abstract: p-Coumalic acid (PCA), caffeic acid (CA), gallic acid (GA) and chlorogenic acid (CGA) are the major phenolic acids that co-exist with soy protein components in foodstuffs. Surprisingly, there are only a handful of reports that describe their interaction with β-Conglycinin (7S), a major soy protein. In this report, we investigated the interaction between phenolic acids and soy protein 7S and observed an interaction between each of these phenolic acids and soy protein 7S, which was carried out by binding. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
4
10
0
Order By: Relevance
“…This means that the contents of tryptophan were decreased by 58.7 and 85 % for WP-CA and WP-RA, respectively. These results are in line with the literatures (You et al 2012, Ali et al 2013, Gan et al 2016. Moreover, the possibility of the interaction of different phenolics with tryptophan has been found , Rawel et al 2002b, Rohn et al 2005, Ali et al 2013).…”
Section: Effect Of the Modification By Ca And Ra On Physiochemical Prsupporting
confidence: 92%
See 2 more Smart Citations
“…This means that the contents of tryptophan were decreased by 58.7 and 85 % for WP-CA and WP-RA, respectively. These results are in line with the literatures (You et al 2012, Ali et al 2013, Gan et al 2016. Moreover, the possibility of the interaction of different phenolics with tryptophan has been found , Rawel et al 2002b, Rohn et al 2005, Ali et al 2013).…”
Section: Effect Of the Modification By Ca And Ra On Physiochemical Prsupporting
confidence: 92%
“…Where, the recorded values were -10.97 ±1.31, -11.13 ±1.32, and -11.35 ±0.65 for UWP, WP-CA, and WP-RA, respectively. All values of zeta potential were negative because the proteins were dissolved in PBS buffer pH 7, this observation is in accordance with Gbassi et al (2012) and Wilde et al (2016). The increase in zeta potential of WP modified by RA was slightly higher than the WP modified by CA.…”
Section: Zeta Potential Of Proteinssupporting
confidence: 82%
See 1 more Smart Citation
“…Although there was no difference in peanut allergen digestibility, IgE‐binding to pepsin‐resistant peptides of Ara h 6 was dramatically reduced (Plundrich and others ). Treatment of soy protein 7S with p ‐coumaric acid, caffeic acid, gallic acid, and chlorogenic acid did not inhibit protein degradation by pepsin at pH 2 and pH 4, and trypsin at pH 7.5, even when the mass ratio of phenolic acids to soy protein 7S reached 10:1 (Gan and others ). Yu and others () demonstrated that casein digestion by pepsin increased with increasing grape seed polyphenol extract (GSP) concentration until GSP concentration reached 0.04 mg/mL, and then decreased.…”
Section: Health Effects Of Plant Phenolic Compoundsmentioning
confidence: 97%
“…In addition, they are also one of the most popular natural antioxidant sources in food industry, as they are label free (clean label); (Xie et al 2017). As discussed previously, phenolic compounds can interact with proteins and these protein-phenol interactions are likely to alter the physiochemical and functional properties of proteins such as the antioxidant activity and surface hydrophobicity, which opens new opportunities for functional ingredients (Ali et al, 2013;Cao & Xiong, 2017;Cao, Xiong, Cao, & True, 2018;Gan et al, 2016;Jia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%